3d gravity as a random ensemble - Jafferis, Daniel L.; Rozenberg, Liza; Wong, Gabriel (The journal of high energy physics, 2025)
A bstract We give further evidence that the matrix-tensor model studied in [1] is dual to AdS 3 gravity including the sum over topologies. This provides a 3D version of the duality between JT gravity and an ensemble of random Hamiltonians, in which the matrix and tensor provide random CFT 2 data subject to a potential that incorporates the bootstrap constraints. We show how the Feynman rules of the ensemble produce a sum over all 3-manifolds and how surgery is implemented by the matrix integral. The partition functions of the resulting 3d gravity theory agree with Virasoro TQFT (VTQFT) on a fixed, hyperbolic manifold. However, on non-hyperbolic geometries, our 3d gravity theory differs from VTQFT, leading to a difference in the eigenvalue statistics of the associated ensemble. As explained in [1], the Schwinger-Dyson (SD) equations of the matrix-tensor integral play a crucial role in understanding how gravity emerges in the limit that the ensemble localizes to exact CFT’s. We show how the SD equations can be translated into a combinatorial problem about 3-manifolds.